Neuromonitoring in Spinal Deformity Surgery: A Multimodality Approach. Issue 1 (February 2018) - Laratta, Joseph L.; Ha, Alex; Shillingford, Jamal N.; Makhni, Melvin C.; Lombardi, Joseph M.; Thuet, Earl; Lehman, Ronald A.; Lenke, Lawrence G.
Study Design: Literature review. Objective: The aim of this study was to provide an overview of the available intraoperative monitoring techniques and the evidence around their efficacy in vertebral column resection. Methods: The history of neuromonitoring and evolution of the modalities are reviewed and discussed. The authors' specific surgical techniques and preferred methods are outlined in detail. In addition, the authors' experience and the literature regarding vertebral column resection and surgical mitigation of neurologic alarms are discussed at length. Results: Risk factors for signal changes have been identified, including preoperative neurologic deficit, severe kyphosis, increased curve magnitude, and significant cord shortening. Even though no evidence-based treatment algorithm exist for signal changes, strategies are discussed that can help prevent alarms and address them appropriately. Conclusion: Through implementation of multimodal intraoperative monitoring techniques, potential neurologic injuries are localized and managed in real time. Intraoperative monitoring is a valuable tool for improving the safety and outcome of spinal deformity surgery.